Pengaruh Media Rolling Ball terhadap Hasil Belajar PAI Siswa Kelas VIII DI SMP Negeri O Mangunharjo Kabupaten Musi Rawas - Muhamad Akip; Rika Astuti; Muhamad Faizul Amirudin (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
The problem in this study is that during the learning process the teacher still uses improvised media such as books or student worksheets and blackboards. The purpose of this study was to determine the effect of rolling ball media on Islamic religion learning outcomes of class VIII students at SMP O Mangunharjo, Musi Rawas Regency. The design used in this study is pretest-posttest control group design. The results showed that classes that used rolling ball media got higher learning outcomes than classes that did not use rolling ball media. The average student learning outcomes at the post-test experimental class > control class (85.6 > 73.7). Based on the t-test analysis using the SPSS application in the final test with an error rate of 5%, the significance value was <0.05 (0.005 <0.05), then Ho was rejected and Ha was accepted. Thus, it can be concluded that there is a significant effect of using rolling ball media on Islamic religion lesson learning outcomes for class VIII students of SMP O. Mangunharjo, Musi Rawas Regency.